Probability and stattistics for engineers and scientists - Hayter, Anthony (Thomson Brooks/Cole, 2007)
This introduction to probability and statistics for engineering and science students focuses on the fundamental concepts of statistical analysis, not on mathematical details or obscure techniques. The sequence of topics will fit almost all one-semester applied probability and statistics courses. The clear, thorough presentation of basic concepts is balanced by a wealth of applied examples and problems. Numerous in-text examples, problems, and real-life applications and illustrations demonstrate how a variety of computer-based statistical software packages (including Minitab) may be used in statistical analysis.